'How much more must I suffer?': post-traumatic stress and the lingering impact of violence upon enslaved people. (3rd April 2021) - Parry, Tyler D.
ABSTRACT: By centering the voices of formerly enslaved people, this article suggests that black Americans in the nineteenth century had a sophisticated understanding of how slavery's brutality instituted a multi-generational legacy of trauma in the United States. While they would not recognize the term 'post-traumatic stress disorder (PTSD), black writers' detailed descriptions of traumatic violence, and its debilitating impact amongst their friends and relatives, reflect many symptoms associated with PTSD. Inspired by the Black Lives Matter movement and its call to examine the lethal repercussions of systemic racism, this article provides one approach for scholars examining the links between anti-black racism and trauma in early American history.